2019
DOI: 10.18410/jebmh/2019/100
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Pulmonary Eosinophilia- An Elaborate Case Series

Abstract: HOW TO CITE THIS ARTICLE: Utpat KV, Sanghavi P, Desai UD, et al. Tropical pulmonary eosinophilia-an elaborate case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Most patients show marked symptomatic, functional, and radiographic improvement after three weeks [ 2 ]. The analysis of a case series showed that response in laboratory and lung function parameters following treatment was variable [ 12 ]. An incomplete response results from persistent low-grade inflammation that leads to interstitial fibrosis and chronic respiratory insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients show marked symptomatic, functional, and radiographic improvement after three weeks [ 2 ]. The analysis of a case series showed that response in laboratory and lung function parameters following treatment was variable [ 12 ]. An incomplete response results from persistent low-grade inflammation that leads to interstitial fibrosis and chronic respiratory insufficiency.…”
Section: Discussionmentioning
confidence: 99%